Educação especial na formação em educação física : um olhar sobre os planos de ensino das licenciaturas paranaenses - Ranzan, Mayara Erbes (Universidade Federal de São Carlos, 2018)
With the intent of increasing debates and reflections about the formation of professors on Physical Education courses and the relationship of this formation at work with disabled people, the current study seeks to analyze the discipline’s teaching plan focused on the acting with this segment, to identify its present reality, in the State of Parana’s context. Thus, this study’s objective is to identify and analyze the aspects that involve specific disciplines, with the purpose of gathering current information on how the latter are built. The collected material was analyzed having as a guided principle the contribution of the disciplines directed to disable people for the formation of Physical Education professionals. After going through some search steps, the object of study was achieved, which contemplates twenty-one Institutions that fits the profile desired to this study. The units intended in the teaching plans in question, are referred as workload, period and regimen in which the course is ministered, courses’ objective, program content and the utilized methodologies. The analyzed data was developed from a qualitative focus, anchored in documental research. The analyzed results checked for the most part, coherence in the elaboration of the teaching plans, when compared to the objective-content programmatic-methodology units. However, when encountered with program content and available workloads, it is believed these units are not in harmony, considering that the extended content for a workload is not always compatible with purposed. In this perspective, it’s convenient to reflect, based on interdisciplinarity, to suggest an important option for the formation’s enrichment. As broad as the workload might be for a specific discipline, it will not contemplate by itself all its diversity, complexity and magnitude in which the area implies. It’s considered relevant the interlocution that the specific course might have with other courses, dividing the content in a way that provides a more complete, dynamic and enriched formation.
Keywords: Educação especial; Educação física; Formação de professores em educação física; Planos de ensino de educação física; Pessoas com deficiência; Special education; Physical education; Formation of physical education professors; Physical education’s teaching plans; Disabled people; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO